Flypaper effect pada Belanja Modal Pemerintah Daerah: Analisis Data Panel Kabupaten/Kota di Provinsi Bengkulu - Sonia Otary Zr; Fachruzzaman Fachruzzaman (Lembaga Komunitas Informasi Teknologi Aceh (KITA), Indonesia, 2026)
This study aims to analyze the effect of Local Own-Source Revenue (PAD), the General Allocation Fund (DAU), and the Physical Special Allocation Fund (DAKF) on regional capital expenditure (BM), and to test the presence of the flypaper effect in districts/municipalities of Bengkulu Province during 2019–2024. The study uses a balanced panel dataset of 10 local governments over six years (60 observations), with all variables transformed into natural logarithms. The data are analyzed using a random-effects panel regression model with robust inference. The results show that PAD does not have a significant effect on capital expenditure, while DAU and DAKF have positive and significant effects. A Wald test on coefficient restrictions indicates that the effect of DAU is statistically more dominant than that of PAD, confirming the presence of the flypaper effect. These findings indicate that capital expenditure in districts/municipalities of Bengkulu Province remains more responsive to intergovernmental transfers than to local own-source revenue. The study implies the need to improve capital expenditure planning quality and strengthen local fiscal capacity to support fiscal independence and better public services.